Artificial Feeding and Laboratory Rearing of Endangered Saproxylic Beetles as a Tool for Insect Conservation. Issue 5 (19th October 2020) - Bonacci, Teresa; Rovito, Mattia; Horák, Jakub; Brandmayr, Pietro
Abstract: Conservation of threatened animals is frequently limited by lack of knowledge about their ecological preferences, and often artificial feeding is one of the few chances to save endangered species. We investigated the possibility to artificially feed two endangered flat bark beetles dependent on dead wood for their diet—namely, Cucujus cinnaberinus (Scopoli, 1763) and Cucujus haematodes Erichson, 1845—by examining their dietary preferences, life cycle duration, and survival in laboratory conditions. Individuals of the two species were caught in the wild and larvae and adults were fed in laboratory conditions by live or dead prey. Three species of saproxylic beetles: two cerambycids ( Acanthocinus griseus Fabricius, 1793 and Rhagium inquisitor Linnaeus, 1758), one scolytid ( Ips sexdentatus Börner, 1776) one tenebrionid ( Tenebrio molitor (Linnaeus, 1758)) one dipteran ( Lucilia sericata (Meigen, 1826)) and one ant ( Lasius sp. Fabricius, 1804) were used as prey, with minced meat as a control. Our results indicated high survival and no difference in prey choice between the two flat beetle species. Larvae and adults preferred dead prey, but no significant preference was detected among dead prey taxa, supporting the hypothesis that the two species are opportunistic scavengers. Comparing data with previous results, both species and their developmental stages should be classified as obligate saproxylic organisms with preference to the dead and decaying organic material. Successful artificial feeding and rearing of these endangered species, followed by the release in the wild through rescue or reintroduction programs, therefore appear relevant for their protection and future conservation. Graphical Abstract: